Respuesta :

b = g + (t-1)w
b-g = (t-1)w
(b-g)/w = t - 1
(b-g)/w + 1 = t
So the last option (as they appear on my laptop)
Solve for t: w(b + g) + 1 = t w(b + g) + 1 = t is equivalent to t = w(b + g) + 1:
Answer:  t = w(b + g) + 1

Solve for t: (b - g)/w = t (b - g)/w = t is equivalent to t = (b - g)/w:
Answer:  t = (b - g)/w

Solve for t: (b + g)/w - 1 = t (b + g)/w - 1 = t is equivalent to t = (b + g)/w - 1: Answer:  t = (b + g)/w - 1
Solve for t: (b + g)/w + 1 = t (b + g)/w + 1 = t is equivalent to t = (b + g)/w + 1: Answer:  t = (b + g)/w + 1